2016
DOI: 10.1002/stem.2338
|View full text |Cite
|
Sign up to set email alerts
|

Fascia Origin of Adipose Cells

Abstract: Adipocytes might arise from vascular stromal cells, pericytes and endothelia within adipose tissue or from bone marrow cells resident in nonadipose tissue. Here, we identified adipose precursor cells resident in fascia, an uninterrupted sheet of connective tissue that extends throughout the body. The cells and fragments of superficial fascia from the rat hindlimb were highly capable of spontaneous and induced adipogenic differentiation but not myogenic and osteogenic differentiation. Fascial preadipocytes expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…ADSC is a population of multipotent cells isolated from adipose tissue [23]. Compared with other sources of stem cells, its advantages are as follows [24][25][26][27]: ① the sources of fat are abundant, ② the patient has less pain and less damage to his donor site, ③ the isolation method of ADSC is simple and the yield is high, which is 1000 times higher than that of bone marrow stem Wexner score of patients, f VAS score of patients; Δ = Absolute value of difference in healing rate between two groups; ns = no significance, ✱✱✱ = p < 0.001, ✱✱ = p < 0.01, ✱ = p < 0.05 cells, ④ ADSC has strong ability to expand in vitro and is easy to be subcultured, ⑤ ADSC has transembryonic differentiation ability, and ⑥ immune rejection of ADSC is lower than that of other stem cells. Since Garcia-Olmo et al [28] first reported the treatment of rectovaginal fistula with adipose stem cell in 2003, this method has been a research hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…ADSC is a population of multipotent cells isolated from adipose tissue [23]. Compared with other sources of stem cells, its advantages are as follows [24][25][26][27]: ① the sources of fat are abundant, ② the patient has less pain and less damage to his donor site, ③ the isolation method of ADSC is simple and the yield is high, which is 1000 times higher than that of bone marrow stem Wexner score of patients, f VAS score of patients; Δ = Absolute value of difference in healing rate between two groups; ns = no significance, ✱✱✱ = p < 0.001, ✱✱ = p < 0.01, ✱ = p < 0.05 cells, ④ ADSC has strong ability to expand in vitro and is easy to be subcultured, ⑤ ADSC has transembryonic differentiation ability, and ⑥ immune rejection of ADSC is lower than that of other stem cells. Since Garcia-Olmo et al [28] first reported the treatment of rectovaginal fistula with adipose stem cell in 2003, this method has been a research hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to BMSCs, this tissue is easily accessible, such as liposuction discarded in liposuction operations, and isolation of stromal cells is relatively simple 4,5 . Similar to the SSCs among BMSCs, the stromal vascular fraction (SVF) of adipose tissue is a heterogeneous population of cells, that include the ASCs, which presumably are similarly associated with SSCs to the microvasculature of fat 6 , in consonance with other tissues in which the adult stem cells are associated with the microvasculature in the form of pericytes 7 . Although several authors claim that ASCs have the inherent ability to differentiate into bonederived cells, to date no research group has demonstrated that this is possible except after transdifferentiating these cells after intensive treatment with BMPs, which has been shown to be a potent osteo-inductor of various cell types 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Rather than serving as just an inert, supporting structure, tissue fascia possesses complex cellular networks. In the rat, for instance, the number of cells, such as adipocytes in the superficial fascia increases with growth (Su et al 2016). These same authors (Su et al 2016) also found that the superficial fascia was home to abundant preadipocytes, capable of differentiating into mature adipocytes and creating a thin adipose layer.…”
Section: Association Between Adipocytes and Mast Cells In Superficialmentioning
confidence: 92%
“…In the rat, for instance, the number of cells, such as adipocytes in the superficial fascia increases with growth (Su et al 2016). These same authors (Su et al 2016) also found that the superficial fascia was home to abundant preadipocytes, capable of differentiating into mature adipocytes and creating a thin adipose layer. This group has now extended these observations to analyze the possible interactions between superficial fascia preadipocytes and mast cells, with the premise that mast cell secretions may aid in preadipocyte-to-adipocyte maturation (Zhang et al 2019).…”
Section: Association Between Adipocytes and Mast Cells In Superficialmentioning
confidence: 92%